Soil humus and aluminum—iron interactions enhance carbon sequestration and yield sustainability after long-term fertilization in three different soils - Philip T. Singbah; Jing Huang; Imtiaz Ahmed; Mahmoud Abdelaziz; Kiya Adare Tadesse; Nano Alemu Daba; Jiwen Li; Jun Yan; Shujun Liu; Lisheng Liu; Huimin Zhang (Journal of Agriculture and Food Research)
Background: The interactions between soil humus and aluminum (Al) and iron (Fe) are critical for regulating soil pH, soil organic carbon (SOC) sequestration, and yield sustainability. However, the underlying mechanisms in different soils and fertilization systems remain inadequately understood. Objective: This study aimed to (i) evaluate the interactions between soil humus and Al–Fe, (ii) analyze their influence on SOC sequestration and yield sustainability, and (iii) identify mechanisms to manage different soils for improving SOC stocks and crop yields. Methods: A long-term field experiment initiated in 1982 at Qiyang Red Soil Experimental Station in southern China was selected. Six fertilization treatments were applied: CK-T (straw take away), CK-R (straw return), NPK-T (NPK with straw take away), NPK-R (NPK with straw return), OM-T (straw take away), and OM-R (straw return). Results: Humic acid carbon (HA-C) and fulvic acid carbon (FA-C) significantly (P < 0.01) regulated Al–Fe concentrations in granite and Quaternary red soils compared to humin carbon (HU-C). Compared to CK-T, NPK-R increased sweet potato yield (Ipomoea batatas 'Beauregard') by 241% and 379% in granite and Quaternary red soils, respectively, while OM-R enhanced broad bean yield (Vicia faba 'Aquadulce Claudia') by 262% and 598%. In purple sandy shale soil, NPK-R improved sweet potato and broad bean yields by 242% and 338%, respectively. Sustainable yield index (SYI) of broad bean exhibited strong (P < 0.01) positive relationship with carbon sequestration rate (CSR). SYI of sweet potato positively (P < 0.05) correlated with CSR only in purple sandy shale soil and negatively in granite and Quaternary red soils. Conclusion: Soil humus regulates Al–Fe interactions, enhancing SOC sequestration and yield sustainability. NPK-R and OM-R were most effective treatments for improving SOC stocks and crop yields in three soils. Significance: Our study provides practical guidance for soil-specific fertilization and organic matter management strategies to increase SOC stocks, nutrient availability, and yield sustainability.